Efficacy of three trap crops against whitefly to manage tomato yellow leaf curl virus (Bangladesh Journal of Agricultural Research, 2008)
doi:10.3329/bjar.v33i3.1610 Bangladesh J. Agril. Res. 33(3) : 515-517, September 2008